AKIBAT HUKUM KELALAIAN NASABAH DALAM PENGGUNAAN APLIKASI BRIMO TERHADAP PERLINDUNGAN DATA PRIBADI - Muhammad Erlangga Syaifutra; Men Wih Widiatno (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Digital transformation in the banking sector has encouraged the widespread use of mobile banking services as a primary means of financial transactions. BRImo, a mobile banking application developed by Bank Rakyat Indonesia (BRI), is one of the most widely used platforms; however, its increasing use also heightens the risk of personal data leakage and misuse. Various cases indicate that losses experienced by customers are often caused by user negligence, such as sharing One Time Passwords (OTP) with unauthorized parties or failing to exercise caution when accessing the application. This study aims to examine the legal consequences of customer negligence in the use of the BRImo application with respect to personal data protection, as well as to assess the extent of the bank’s legal responsibility under such circumstances. The research employs a normative juridical method with statutory and conceptual approaches, based on a literature review of primary and secondary legal materials. The regulations analyzed include Law Number 27 of 2022 on Personal Data Protection, the Law on Electronic Information and Transactions, and Financial Services Authority regulations concerning consumer protection in the financial services sector. The findings indicate that the Indonesian legal framework clearly stipulates customers’ obligations to maintain the confidentiality of authentication data and to apply the principle of prudence. When customer negligence is proven to be the primary cause of loss, legal liability is not fully imposed on the bank. This study emphasizes that personal data protection in mobile banking is proportional in nature and requires active participation and awareness from customers. Keywords: mobile banking, personal data, customer negligence, BRImo Abstrak: Transformasi digital di sektor perbankan telah mendorong penggunaan layanan mobile banking sebagai sarana utama transaksi keuangan masyarakat. Aplikasi BRImo milik Bank Rakyat Indonesia (BRI) menjadi salah satu platform yang banyak digunakan, namun di sisi lain meningkatkan potensi risiko kebocoran dan penyalahgunaan data pribadi nasabah. Berbagai kasus menunjukkan bahwa kerugian yang dialami nasabah sering kali disebabkan oleh kelalaian pengguna, seperti memberikan kode One Time Password (OTP) kepada pihak lain atau kurangnya kehati-hatian dalam mengakses aplikasi. Penelitian ini bertujuan untuk mengkaji akibat hukum kelalaian nasabah dalam penggunaan aplikasi BRImo terhadap perlindungan data pribadi serta menilai sejauh mana tanggung jawab hukum bank dalam kondisi tersebut. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual, melalui studi kepustakaan terhadap bahan hukum primer dan sekunder. Regulasi yang dianalisis meliputi Undang-Undang Nomor 27 Tahun 2022 tentang Pelindungan Data Pribadi, Undang-Undang Informasi dan Transaksi Elektronik, serta Peraturan Otoritas Jasa Keuangan terkait perlindungan konsumen sektor jasa keuangan. Hasil penelitian menunjukkan bahwa sistem hukum Indonesia telah mengatur kewajiban nasabah untuk menjaga kerahasiaan data autentikasi dan menerapkan prinsip kehati-hatian. Apabila kelalaian nasabah terbukti sebagai penyebab utama kerugian, maka tanggung jawab hukum tidak sepenuhnya dibebankan kepada bank. Penelitian ini menegaskan bahwa perlindungan data pribadi dalam mobile banking bersifat proporsional dan memerlukan peran aktif dari nasabah. Kata kunci: mobile banking, data pribadi, kelalaian nasabah, BRImo.